High-fidelity numerical modelling of ocean wave energy systems: A review of computational fluid dynamics-based numerical wave tanks. (October 2018) - Windt, Christian; Davidson, Josh; Ringwood, John V.
Abstract: For the research and development (R&D) of wave energy converters (WECs), numerical wave tanks (NWTs) provide an excellent numerical tool, enabling a cost-effective testbed for WEC experimentation, analysis and optimisation. Different methods for simulating the fluid dynamics and fluid structure interaction (FSI) within the NWT have been developed over the years, with increasing levels of fidelity, and associated computational expense. In the past, the high computational requirements largely precluded Computational Fluid Dynamics (CFD) from being applied to WEC analysis. However, the continual improvement and availability of high performance computing has led to the steady increase of CFD-based NWTs (CNWT) for WEC experiments. No attempt has yet been undertaken to comprehensively review CNWT approaches for WECs. This paper fills this gap and presents a thorough review of high-fidelity numerical modelling of WECs using CNWTs. In addition to collating the published literature, this review tries to make a step towards a best practice guideline for the applications of CFD in the field of wave energy. Abstract : Highlights: A comprehensive review of CFD-based numerical wave tanks (CWNTs) for wave energy converter (WEC) experiments is presented. The published literature is reviewed and categorised based on important features and requirements of CWNTs for WEC experiments. Based on the reviewed literature best practice guidelines are presented. Based on the reviewed literature deficits of currently used CNWTs are identified and routes to their solution are suggested.